Techno-economic Viability and Energy Conversion Analysis of RHES with Less Weight/Area - Mohammed Kdair Abd; Hadeel Nasrat Abdullah; Haishun Sun; Shijie Cheng (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This article proposes a new strategy to find the optimal location, configuration and size of the Renewable (wind-photovoltaic-diesel-battery) Hybrid Energy Systems (RHES (off-grid)). This study has two steps: first, the proposaltoa strategybased on a weather change to find the optimal location in Iraq using Hybrid Optimization Model for Electric-Renewables (HOMER) software. Second, the study will examine the influence of the techno-economic viability from side less weight and area on the optimal configuration/size of the RHES, which gives the maximum output power. A period of one-year for meteorological data for both solar radiation and wind speed has used. Finally, simulation results indicated that the optimal location for this RHES is the AL Harithah location. The analysis has shown that RHES can supply 89% of the load demands by renewable-energy. It is also successful in reducing the area required for installation of the RHES about 28%.